Towards a new model of Radio Business: Corporate Radio - Peinado-Miguel, Fernando; Rodríguez-Barba, Dolores; Rodríguez-Pallarés, Miriam (Estudios sobre el Mensaje Periodístico, 2017)
The economic crisis that originated at the beginning of this century has caused major changes in the communications market, and affected companies, media professionals and other stakeholders in the sector of cultural industries. In the case of Radio, the study by MediaCom UCM develops a comparative analysis of different ways to generate radio content today from digital technology platforms, audiovisual examples of innovation and also maintain different business strategies in the so-called Corporate Radio. A methodology of qualitative research based on in-depth interviews and indirect observation of different cases under study is applied. The results show us new perspectives for the Radio Company and new scenarios for the development of this activity